INTERACTION OF T-LYMPHOCYTES OF CD4+CD27HI AND CD4+CD27LO WITH MACROPHAGES IN TUBERCULOUS INFECTION IN MICE - G. S. Syepel'kova; K. B. Mayorov; V. V. Evstifeev; A. S. Apt (Туберкулез и болезни лёгких)
Greatly the protective immune response in tuberculosis is defined by the ability of activated pulmonary macrophages of the host to suppress the mycobacterial growth. Macrophages are activated by the action of cytokines and other inflammatory mediators, in particular IFN-γ and TNF-α, secreted by T-lymphocytes. There are two different populations of effector lymphocytes of CD4+CD62LloCD44hi, one of them has the surface phenotype of CD27hi, and the other – CD27lo. Early the experimental model of tuberculous infection has shown that these types of cells have different vitality and abilities to produce inflammatory cytokines of IFN-γ and TNF-α. The effect of these cells on bacteriostatic activity of macrophages has been studied. It has been shown that Т-lymphocytes of CD27lo are much more effcient activating macrophages and stronger promote formation of active nitrogen forms. Activating action of the effectors of CD27lo was observed even when the ratio of macrophages and T-cells made 625 : 1. With this ratio the active nitrogen forms have not been detected thus one can conclude that there is one more nitrogen independent activation mechanism.